(untitled) (Research, Society and Development, 2021)
Objective: to analyze the available scientific productions on school health actions that have been recommended for the reopening of educational institutions in the context of the COVID-19 pandemic. Method: This is a narrative literature review carried out between June and July 2020 in the MEDLINE, LILACS, BDENF and Scopus databases. Main results: The initial search resulted in 65,246 publications, and the final sample consisted of seven articles. Prevention, promotion, and health surveillance actions were identified with a focus on controlling the dissemination of SARS-CoV-2 in the school environment. Conclusion: This review evidenced a notable scarcity of high-level studies that would be needed to support the safe reopening of schools, as well as the development of consolidated and well-structured guidelines and protocols bringing health responsibility with measures to prevent and minimize the effects and control of the spread of the SARS-CoV-2.